INTERNAL CYLINDRICAL SURFACES ARE MACHINED USING A GRINDER - Akyulova Nigora Inobidin daughter (American Journals Publishing, 2025)
This in the article different kind Internal cylindrical to surfaces thorns with processing to give process own inside. For continuous machining of holes, the following methods are used: boring and milling. Depending on the number of teeth (rings) of the straightening and tightening dies, boring dies are divided into single-ring and multi-ring. Figure 333 shows the types of straightening and tightening dies. Single-ring and multi-ring boring dies (rings) by their design allow boring holes only within certain values of tension (the difference between the surface diameter of the tool and the inner diameter of the hole)Objective: To identify technological deficiencies and defects in mandrels and recommend advanced techniques and technologies for their improvement, as well as to increase labor efficiency by introducing them into production and increasing their service life.Conclusion. Machining internal cylindrical surfaces using a grinderThe use of the boring technological process can improve the efficiency of the workpiece. At the same time, it is possible to increase surface cleanliness, reduce waste, and increase productivity. The widespread use of the boring process in mechanical engineering, aircraft construction, and the production of military weapons ensures that our products comply with these standards.